The Influence Of Elderly Exercise On The Quality Of Life Of The Elderly At Bontonompo 1 Health Center In Pa'bundukang Village - Asriadi; Noyumala (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Background: Elderly exercise is low impact aerobic exercise, light to moderate intensity, the movements involve most of the body's muscles, in accordance with daily movements, movements between right and left receive a balanced load while quality of life is the individual's perception of position in life in the context of culture and the value systems adopted. Research Objective: To determine the influence of elderly exercise on the quality of life of the elderly at the Bontononpo 1 health center in Pa'bundukang village. Method: The type of research used in this research is quantitative descriptive research with pre-experiments. Meanwhile, the research design used is a one-shot case study, namely an experiment carried out without a comparison group and also without an initial test. The total population is 120 people, this research sample was taken using a porpusive sampling technique, a sampling technique based on the wishes of the researcher, the data measurement tool used a questionnaire. Research results: There is an influence of elderly exercise on the quality of life of the elderly at the Bontononpo 1 health center in Pa'bundukang village showing a value of (0.004˂ 0.05). Conclusion: There is an influence of elderly exercise on the quality of life of the elderly at the Bontononpo 1 health center in Pa'bundukang village.